Interharmonic Analysis Model of Photovoltaic Grid-connected System with Extended Dynamic Phasors - Qing Zhong (IEEE, 2021)
The interactions between randomly fluctuating power outputs from photovoltaic (PV) at the DC side and background voltage distortions at the AC side could generate interharmonics in the PV grid-connected system (PVGS). There is no universal method that can reveal the transmission mechanism of interharmonics and realize accurate calculation in different scenarios where interharmonics exist in the PVGS. Therefore, extended dynamic phasors (EDPs) and EDP sequence components (EDPSCs) are employed in the interharmonic analysis of the PVGS. First, the dynamic phasors (DPs) and dynamic phasor sequence components (DPSCs) are extended into EDPs and EDPSCs by selecting a suitable fundamental frequency other than the power frequency. Second, an interharmonic analysis model of the PVGS is formulated as a set of state space equations. Third, with the decoupling characteristics of EDPSCs, generation principles and interactions among the interharmonics in the PVGS are presented by the sequence components, and its correctness is verified by simulation and experiment. The presented model can be used to accurately calculate the interharmonics generated in the PVGS both at the AC and DC sides. Because of the decoupling among the EDPSCs, the set of state space equations can effectively describe the principle.